Wednesday

April 16, 2014

April 16, 2014

Posted by **angie** on Thursday, February 16, 2012 at 11:31am.

- Calculus -
**MathMate**, Thursday, February 16, 2012 at 2:44pmUse implicit differentiation:

sin^-1(xy)=cosy

sin(cos(y))=xy

differentiate both sides with respect to x

(use chain rule):

cos(cos(y))(-sin(y))y'=y+xy'

Collect terms and solve for y'

y'=-y/(cos(cos(y))sin(y)+x)

**Related Questions**

integral Calculus - ʃsin y dy/ √1 + cosy please help..thanks.. that's...

Calculus - Find the dervatives: 1. f(x)=(3x+1)e^x^2 2. y = e^(sin x) ln(x) 3. f(...

Pre-calculus - If cosx=4/5, cosy=12/13 in Quad. IV, find sin(x+y)

Pre-calculus - If cosx=4/5, cosy=12/13 in Quad. IV, find sin(x+y)

calc - what is the derivative of sinx- cosy = 0 in its simplest form? I got to ...

Trigonometry Help - Simplify: sin(x-y)cosy+cos(x-y)siny = (sinxcosy-cosxsiny)...

calculus - Find the equation of the tangent to the curve sin(x+y)=xy at the ...

Calculus - How would you find the derivative of this implicit function? 1+x=sin(...

Calculus - Consider the function f(x)=sin(1/x) Find a sequence of x-values that ...

Calculus - Find dy/dx using implicit differentiation of xy + sin^2y=10350. Is it...